Child Sexual Abuse, Disclosure and Reintegration: Too Late or Too Soon. - Mbakogu, Ifeyinwa; Odiyi , Lotanna (Journal of Social Work Education and Practice, 2023)
There is a lot of news reporting in Nigeria on the sexual abuse of children, especially the female child. Several of these abuses occur during domestic work or in children’s family homes with perpetrators who could be close family members (parents, siblings or distant relatives), friends, neighbours, teachers or strangers. Bearing in mind that child sexual abuse is a social issue that could benefit from a more nuanced understanding of the problem, children facing sexual abuse are better positioned to provide critical insight into their diverse experiences and triggers of the problem. It is essential to speak to affected children to understand factors reinforcing their abuse and the nature of resources available and desired by them for effective reintegration or adjustment after exiting protection offered by anti-trafficking shelters. The paper interacts with African Centred approaches as studies indicate that the peculiarities of the African culture manifested in Ubuntu, have a significant effect on the incidence and disclosure rates of child sexual abuse in Africa, the recently instituted Nigeria Sex Offender’s Registry, and children’s diverse narratives for a critical discussion on the problem. Several themes generated from the findings highlight the link between child labour and child susceptibility to sexual abuse. The findings also indicate the trauma of disbelief, stigma, culture of silence or lack of disclosure surrounding and reinforcing children’s encounter with sexual exploitation. These narratives limit the nature of children’s reintegration with families after disclosure of sexual experiences and should shape the direction of interactions for addressing children’s problems. ​